HAKIKAT MANUSIA DALAM PENDIDIKAN ISLAM - Nisa Pangesti Br Tarigan, Giva; Limbong, Rezxi; Wiryanti Siregar, Wika; Hanum OK, Azizah (Universitas Maritim AMNI Semarang, 2022)
Educating is the duty, mandate, and responsibility of parents, teachers, or authorized educators. in any environment and situation, an educator must make students able to absorb and understand the material and teaching that is directed and conveyed. In addition, the totality of teaching staff is also a capital in achieving the expected educational goals. Educational work is not only a family obligation, but also an obligation for educators in schools. school as a formal educational institution in the sense that it is carried out on the basis of strong regulations and with certain conditions and a certain basis.